Utilization of ICT in 21st Century Learning in Elementary Schools - Hartami, Yustalena (Elementary Education Journal, 2024)
Background:This study aims to describe studies related to how ICT is utilized and the obstacles to the utilization of ICT in 21st century learning in elementary schools. Method:This study uses a qualitative descriptive approach and a type of library research or (literature review). The data analysis technique used is content analysis. The validity of the data used is the persistence of observation and triangulation of sources. Result:The results of the study indicate that the use of ICT in 21st century learning in elementary schools is (1) ICT is used to find models, methods, strategies in compiling learning plans; (2) Teachers use ICT as a source of information; (3) Students use ICT as a learning resource; (4) Teachers use ICT to visualize abstract materials; (5) Teachers use ICT to conduct e-learning (6) Teachers use ICT to make learning more interesting and enjoyable while the obstacles in the use of ICT in 21st century learning in elementary schools are (1) Lack of teacher competence in integrating technology in learning; (2) Not all class teachers have the ability in programming languages; (3) Teachers' perceptions that the use of ICT has no benefits (4) The number of ICT-based media is still lacking; (5) IT facilities are inadequate; (6) Rural areas use used multimedia devices that have old specifications and are lagging behind current ICT developments. Keywords: Utilization of ICT, 21st Century Learning, and Literature Research (library research) or (literature review). Implication:This study has implications that elementary schools need to be more serious in utilizing ICT for 21st century learning. Teachers need to be supported with adequate training and facilities so that they are able to use ICT optimally in learning. In addition, the government and related parties need to pay attention to the technological gap, especially in rural areas that still use old devices. Teachers also need to be encouraged to change the view that ICT is not a burden, but a tool that can make learning more interesting and effective. Novelty:This research is a systematic presentation of the benefits and constraints of using ICT in 21st century learning in elementary schools using a literature study approach.